Kompetensi Kewarganegaraan Berbasis Keterampilan Abad 21 dalam Pendidikan Kejuruan: Kompetensi Kewarganegaraan Berbasis Keterampilan Abad 21 dalam Pendidikan Kejuruan - Eneng Martini Eneng (Fakultas Seni Rupa dan Desain ITB, 2023)
The 21st century’s skills-based education is called the knowledge era, and every academic graduate must be prepared to compete with the outside world. So, at this time, ready-to-use citizenship competence is needed to be a citizen who is not left behind with the progress of the times. This study used a qualitative approach, and the object of this study was a vocational high school (SMK), with data collection consisting of interviews, observations, and literature studies with locations in Bandung. A total of 15 informants were involved, divided into school principals, teachers, and students. The results in the field show that the PPKn learning material in vocational high schools is too broad and there is overlapping material, so civic competence must be increased according to the needs of the times. 21st century, digital literacy, technology, and character.